DEVELOPING INDEPENDENT MEDIA EDUCATION THROUGH ONLINE PLATFORMS (YOUTUBE, COURSERA) - Tog’ayeva Muattar Bahodir qizi, (TADQIQOTLAR, 2026)
Annotation: The rapid development of digital technologies has transformed the educational landscape, enabling learners to access knowledge independently through online  platforms.  This  article  explores  the  role  of  platforms  such  as  YouTube  and Coursera in fostering independent media education. The study examines how these platforms contribute to the development of media literacy, critical thinking, and self-directed learning skills. Using a mixed-method approach, including content analysis and learner feedback, the research highlights the effectiveness of online platforms in enhancing  media  competence.  The  findings  indicate  that  these  platforms  provide flexible, accessible, and diverse learning opportunities, although challenges such as information  overload  and  lack  of  guidance  remain.  The  article  concludes  with recommendations for optimizing the use of online platforms in media education.